2016
DOI: 10.1007/s40894-016-0041-0
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Approaches to Research on Bullying in Adolescence

Abstract: Bullying is a significant public health problem in the United States that affects youth functioning in multiple domains. Much of the research on bullying to date has focused on children, however, leaving gaps in the literature with respect to understanding bullying among adolescents. In particular, less is known about how adolescents conceptualize bullying, what predicts and is associated with bullying involvement among adolescents, and how prevention programs might address the unique needs of middle and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
(50 reference statements)
0
12
0
7
Order By: Relevance
“…Desde diferentes perspectivas con la intención de esclarecer sobre qué variables se han de intervenir. Sin embargo, de acuerdo con Holt et al (2017) la mayor parte de los estudios existentes hasta la fecha se centran en el análisis de este fenómeno durante la educación primaria, siendo necesario seguir avanzando en el estudio del acoso y ciberacoso durante la educación secundaria, ámbito sobre el que se circunscribe esta investigación. Bradshaw (2015) por su parte ha reforzado esta idea insistiendo en la necesidad de avanzar hacia programas más efectivos de prevención y resolución de conflictos en las instituciones educativas, basados en los hallazgos que se extraigan de un mayor volumen de estudios que amplíen la evidencia sobre la estrategia más práctica para poner fin al acoso escolar y al ciberacoso.…”
Section: De Acuerdo Conunclassified
“…Desde diferentes perspectivas con la intención de esclarecer sobre qué variables se han de intervenir. Sin embargo, de acuerdo con Holt et al (2017) la mayor parte de los estudios existentes hasta la fecha se centran en el análisis de este fenómeno durante la educación primaria, siendo necesario seguir avanzando en el estudio del acoso y ciberacoso durante la educación secundaria, ámbito sobre el que se circunscribe esta investigación. Bradshaw (2015) por su parte ha reforzado esta idea insistiendo en la necesidad de avanzar hacia programas más efectivos de prevención y resolución de conflictos en las instituciones educativas, basados en los hallazgos que se extraigan de un mayor volumen de estudios que amplíen la evidencia sobre la estrategia más práctica para poner fin al acoso escolar y al ciberacoso.…”
Section: De Acuerdo Conunclassified
“…In our research, when we say youth we are considering people between the ages of 18 and 30 years who are studying in universities in New Zealand. As indicated in US national data, approximately 15% of youth have been victims of cyberbullying [4]. As relevant to our research, from previous New Zealand based statistics, 2.6% among 826 participants were bullied in the span of six months in New Zealand where more males were victimized than females on social networking sites (SNS) [5].…”
Section: Introductionmentioning
confidence: 85%
“…On the other hand, in exploring cyber-bullying [23] there were no statistically significant gender differences to be found, while the research has revealed that in all forms of traditional violence and cyber-bullying the bullies were usually older students. The research has shown that, apart from gender and age, modest school success is a risk determinant of traditional violent and aggressive behavior among preadolescents, where bullies follow school's house rules, have bad communication with teachers, bad grades, and a large number of unexcused absences [24].…”
Section: Introduction mentioning
confidence: 99%